Characterization of a prototype MR-compatible Delta4 QA system in a 1.5 tesla MR-linac. (11th January 2018) - de Vries, J H W; Seravalli, E; Houweling, A C; Woodings, S J; van Rooij, R; Wolthaus, J W H; Lagendijk, J J W; Raaymakers, B W
Abstract: To perform patient plan quality assurance (QA) on a newly installed MR-linac (MRL) it is necessary to have an MR-compatible QA device. An MR compatible device (MR-Delta4) has been developed together with Scandidos AB (Uppsala, Sweden). The basic characteristics of the detector response, such as short-term reproducibility, dose linearity, field size dependency, dose rate dependency, dose-per-pulse dependency and angular dependency, were investigated for the clinical Delta4-PT as well as for the MR compatible version. All tests were performed with both devices on a conventional linac and the MR compatible device was tested on the MRL as well. No statistically significant differences were found in the short-term reproducibility (<0.1%), dose linearity (⩽0.5%), field size dependency (<2.0% for field sizes larger than 5 × 5 cm 2 ), dose rate dependency (<1.0%) or angular dependency for any phantom/linac combination. The dose-per-pulse dependency (<0.8%) was found to be significantly different between the two devices. This difference can be explained by the fact that the diodes in the clinical Delta4-PT were irradiated with a much larger dose than the MR-Delta4-PT ones. The absolute difference between the devices (<0.5%) was found to be small, so no clinical impact is expected. For both devices, the results were consistent with the characteristics of the Delta4-PT device reported in the literature (Bedford et al 2009 Phys. Med. Biol .54 N167–76; Sadagopan et al 2009 J. Appl. Clin. Med. Phys .10 2928). We found that the characteristics of the MR compatible Delta4 phantom were found to be comparable to the clinically used one. Also, the found characteristics do not differ from the previously reported characteristics of the commercially available non-MR compatible Delta4-PT phantom. Therefore, the MR compatible Delta4 prototype was found to be safe and effective for use in the 1.5 tesla magnetic field of the Elekta MR-linac